THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING MODELS IN IMPROVING STUDENT LEARNING OUTCOMES IN JUNIOR HIGH SCHOOLS - Nur Adilah; slamet Riyadi; Suwardi, Suwardi (Journal of Social and Economics Research, 2024)
This research aims to systematically examine the effectiveness of the contextual learning model in improving Islamic Religious Education learning outcomes for junior high school (SMP) students. Apart from that, this research also wants to identify the factors that influence the success of implementing this learning model. This research uses a Systematic Literature Review approach. Data was obtained through searching for relevant literature from the Scopus data base in the 2019-2024 publication time period using keywords such as "Contextual Teaching and Learning (CTL)", "Islamic Religious Education", "learning outcomes", and "SMP". Thirty-five articles were found that met the inclusion criteria and were then analyzed in depth. The data analysis techniques used include thematic analysis to identify patterns and themes that emerge in various studies. The results of the analysis show that the application of the contextual learning model is consistently able to improve Islamic Religious Education learning outcomes for junior high school students. This increase in learning outcomes is associated with several factors, including: i) Increased learning motivation. Students become more motivated because learning material is linked to real life. ii) Increased learning activities. Students are more actively involved in the learning process, such as discussions and problem solving. iii) Increased understanding of concepts. It is easier for students to understand the concepts in Islamic Religious Education because learning is carried out contextually. The contextual learning model can be an effective alternative for improving the quality of Islamic Religious Education learning. Teachers, schools and policy makers need to pay more attention to the implementation of this learning model.